2021
DOI: 10.3390/cancers13040786
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based HPV Status Prediction for Oropharyngeal Cancer Patients

Abstract: Infection with the human papillomavirus (HPV) has been identified as a major risk factor for oropharyngeal cancer (OPC). HPV-related OPCs have been shown to be more radiosensitive and to have a reduced risk for cancer related death. Hence, the histological determination of HPV status of cancer patients depicts an essential diagnostic factor. We investigated the ability of deep learning models for imaging based HPV status detection. To overcome the problem of small medical datasets, we used a transfer learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 47 publications
0
22
1
Order By: Relevance
“…No researcher registered a prospective study in a trial database or performed a cost-effectiveness analysis, but 4 investigators did share the data obtained. Elhalawani shared the dataset generated for the study in Figshare repository [ 22 ], other authors share the code [ 23 , 24 ], while Suh shared the datasets and the analysis on reasonable request [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…No researcher registered a prospective study in a trial database or performed a cost-effectiveness analysis, but 4 investigators did share the data obtained. Elhalawani shared the dataset generated for the study in Figshare repository [ 22 ], other authors share the code [ 23 , 24 ], while Suh shared the datasets and the analysis on reasonable request [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Deep learning is a subset of machine learning that uses deep neural networks to learn and classify data 9 . Within the context of OPC, deep learning algorithms have been used to predict HPV status based on pre-treatment imaging 10,11 . Although clinical assessment of involved lymph nodes is necessary for therapy disposition and radiotherapy treatment planning, no deep learning algorithms have focused on the identification and segmentation of involved lymph nodes for HPV-associated OPC.…”
Section: Introductionmentioning
confidence: 99%
“…Since the input features are the raw images, there is no need for feature extraction or feature selection as in traditional machine learning. Both techniques (traditional machine learning and DL) have been shown to predict prognosis, tumor progression, molecular aberrations, or spatial infiltration in various cancer subtypes [18][19][20][21][22][23][24]. Some studies found superior predictive performances using CNNs compared to handcrafted features [25,26].…”
Section: Introductionmentioning
confidence: 99%